Rapamycin Alleviates 2, 4, 6-Trinitrobenzene Sulfonic Acid-Induced Colitis through Autophagy Induction and NF-κB Pathway Inhibition in Mice. (18th August 2022) - Ni, Zhen; Li, Hao; Mu, Dong; Hou, Juanni; Liu, Xiaoyan; Tang, Shanhong; Zheng, Shumei
Abstract : Background . Recent genetic studies indicated that variants of autophagy genes were associated with the predisposition of Crohn's disease (CD). The autophagy deficiency may affect the innate and adaptive immunity, which is related to persistent and excessive inflammation of the bowel. However, it remains unclear how autophagy modulates the expression of immune response regulator NF- κ B and proinflammatory cytokine TNF- α in CD. Aim . We aimed to investigate the role of rapamycin on the expression of NF- κ B p65 and TNF- α in 2, 4, 6-trinitrobenzene sulfonic acid (TNBS)-induced mouse colitis and lipopolysaccharide (LPS)-induced HT-29 cells. Methods . TNBS-induced colitis mice were treated with saline or rapamycin, and the disease activity index (DAI) and histological scores of colonic mucosa were evaluated. The expressions of p65, ATG16L1 and LC3 were detected by western blot and immunohistochemistry staining. The monodansylcadaverine (MDC) staining and transmission electron microscopy were developed to study the autophagy in LPS-induced HT-29 cells. Expression of TNF- α from colon tissue and HT-29 cells were detected by ELISA. The expressions of p65, ATG16L1 and LC3 in active CD patients were also investigated. Results . Significantly more autophagosomes were observed in rapamycin-treated cells than in controls. Rapamycin remarkably upregulated the expression of ATG16L1 and LC3II, inhibited p65 nucleus translocation and secretion of TNF- α both in vivo and in vitro . The expression of both ATG16L1 and LC3II increased in mild to moderate CD specimens, while no significant difference was noted between severe CD and normal controls. The expression of p65 increased notably in severe CD compared to those in mild to moderate patients. Conclusions . In LPS-treated HT-29 cells and TNBS-induced colitis, p65 is overexpressed, which results in exaggerated secretion of TNF- α and induce or worsen the inflammation in the bowel. Rapamycin protects against colitis through induction of autophagy, thus inhibiting the activation of NF- κ B pathway and secretion of TNF- α .